Indonesian Bankruptcy Law: Revisited - Wijantini, Wijantini (International Research Journal of Business Studies, 2008)
One of the key challenges in financial distress resolution is to find the way to renegotiate the debts. Financial troubled firms may apply either court or out-of-court resolution process. Under court supervision, firms have to follow Indonesian bankruptcy law which offers a moratorium on debt repayment through a system of court supervision and liquidation proceedings. Alternatively, firms may apply out-of-court workout. This paper is written to examine process of both resolutions, problem in executing the law and the reasons for least likelihood of filing court solution in Indonesia. In addition, it shows study on bankruptcy filing in East Asia countries.